A regional Australasian experience of extended endoscopic transsphenoidal surgery for craniopharyngioma: Progression of the mentoring model. (October 2019) - Gauden, A.J.; Harley, B.; Pears, C.; Wickremesekera, A.; Parker, A.; Robinson, S.; Baguley, C.; Wormald, P.J.
Highlight: Craniopharyngiomata can be treated effectively using endoscopic endonasal trans-sphenoidal approach with satisfactory outcomes. Abstract: Endoscopic endonasal transsphenoidal approaches to craniopharyngioma has become increasingly popular over the last 15 years. We present the results of our retrospective series of craniopharyngiomata resected by an endoscopic, endonasal approach at a low-volume service in Australasia. Between the years of 2009 and 2017, 11 patients underwent pure endoscopic endonasal transsphenoidal resection for a craniopharyngioma at our institutions. The medical records, histopathology, intraoperative findings and patient imaging were retrospectively assessed. 11 patients were included with 5 male and 6 female patients. The mean age was 32.0 years (range 14–68 years). Of this patient series a gross total resection of the tumour was achieved in 8 of 11 patients (73%). In the immediate postoperative phase, 10 of the 11 patients developed diabetes insipidus (91%). The pituitary stalk was formally not seen in 4 patients and all were treated with vasopressin. Of the 7 patients where the pituitary stalk was identified it was formally divided in 6 and preserved in 1 patient where the tumour was separate to the stalk. The endoscopic endonasal transsphenoidal approach for excision of craniopharyngioma, utilising and progressing the surgical mentoring model, can achieve adequate decompression of critical structures. Furthermore, our aggressive approach to divide and remove the involved pituitary stalk results in high rates of gross macroscopic resection with excellent long-term disease control with a greater risk of postoperative diabetes insipidus and panhypopituitarism.